20t-29=6t-11

Simple and best practice solution for 20t-29=6t-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20t-29=6t-11 equation:


20t-29=6t-11

We simplify the equation to the form, which is simple to understand
20t-29=6t-11

We move all terms containing t to the left and all other terms to the right.
+20t-6t=-11+29

We simplify left and right side of the equation.
+14t=+18

We divide both sides of the equation by 14 to get t.
t=1.28571428571

See similar equations:

| 35=s(s-2) | | 8-3(5-2x)=8(x-1)-11 | | (y-4)-(y+5)=8y | | 6c+13=8c | | 3x-(4-x)=8 | | 3u^2-12u+3=0 | | 28a^2=4a | | 36x^2-9x^2= | | -(3-5(-a-3)-7)=[(5-a)-7-8] | | 5t-3(t-2)=t+6 | | 4x^2=4y^2+16 | | (9x)4x= | | 14t+8=8t+14 | | 9x-4(-2)=x+20 | | b(x)+g(y)=j | | -8*0+7y=-56 | | -3.6x-5.9=1.3 | | y=12x+1 | | 4x+5=85-4x | | bx+gy=j | | 268-3x=42x+23 | | q+0.3=-1.1 | | 9-8x=28-15x | | -4v-3=0 | | (4x+1)(6-2x)=x(4-8x) | | 3x+33=10x-51 | | -9v-8=12 | | -10=9v-1 | | -8x+7y=-56 | | 0.8+9.9=6.3 | | -3z+1=-17 | | 0=4w-28 |

Equations solver categories